2013
DOI: 10.1038/eye.2012.294
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adherence behaviour for patients with glaucoma

Abstract: Aims and purpose Adherence to long-term treatment regimens for primary open-angle glaucoma holds a challenge for both clinicians and patients. The study aims were to (i) establish the magnitude of travoprost non-adherence using an Electronic Adherence Monitor (EAM), (ii) compare electronic with patient self-reported adherence, and (iii) explore the application of a previously reported method of graphically presenting adherence data to a larger cohort over a longer monitoring period. Methods A cohort study of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
2
31
0
6
Order By: Relevance
“…Pharmacy refill methods 1012 , electronic monitoring 1319 , and self-report measures 15,18,20 have all been used to assess the medication adherence of glaucoma patients. Estimates of adherence vary based on the method being used; pharmacy refill records have produced the lowest estimates of glaucoma medication adherence while self-report measures have yielded the highest adherence estimates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pharmacy refill methods 1012 , electronic monitoring 1319 , and self-report measures 15,18,20 have all been used to assess the medication adherence of glaucoma patients. Estimates of adherence vary based on the method being used; pharmacy refill records have produced the lowest estimates of glaucoma medication adherence while self-report measures have yielded the highest adherence estimates.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the validity of self-reported measures against objective measures (e.g., pharmacy records or electronic monitors) in glaucoma patients. 15,18 Both studies found that patients with glaucoma tended to over-estimate their adherence to glaucoma medications. 15,18 Furthermore, Cook et al 15 found that the correlation between MEMS and self-report was only 0.31.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tablets can be transferred into dosing boxes to aid the memory, which could be an important resource for elderly patients [127]. Such visual cues or practical remedies are not possible with a bottle of drops [128]. Unit-dose medications in SundayMonday packs would clearly identify missed medications to patients and/or carers, and has been identified as a potential aide to improve adherence (American Glaucoma Society) [129].…”
Section: Administration Of Topical Antiglaucoma Therapies and Prescrimentioning
confidence: 99%